2020
DOI: 10.1007/s13595-020-00996-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing selected microhabitat types on living trees in Oriental beech (Fagus orientalis L.) dominated forests in Iran

Abstract: & Key message On the selected sites in the investigated Oriental beech (Fagus orientalis L.) dominated forests in Iran with an extensive individual tree selection system, tree microhabitats (MH) are more influenced by tree level factors such as tree species and DBH than by plot level factors such as plot basal area or size and species diversity. & Context Despite the ecological importance of tree microhabitats for biodiversity, there is a lack of information about the occurrence of microhabitat features in Hyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
(53 reference statements)
2
8
0
Order By: Relevance
“…In accordance with many previous publications (Asbeck et al., 2019; Khanalizadeh et al., 2020; Kozak et al., 2018; Larrieu & Cabanettes, 2012; Larrieu, Cabanettes, Brin, et al., 2014; Paillet et al., 2019; Regnery et al., 2013; Vuidot et al., 2011), our results confirm that TreMs tend to accumulate on trees during their growth. However, the rate of TreM formation depends on DBH differently from what we expected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with many previous publications (Asbeck et al., 2019; Khanalizadeh et al., 2020; Kozak et al., 2018; Larrieu & Cabanettes, 2012; Larrieu, Cabanettes, Brin, et al., 2014; Paillet et al., 2019; Regnery et al., 2013; Vuidot et al., 2011), our results confirm that TreMs tend to accumulate on trees during their growth. However, the rate of TreM formation depends on DBH differently from what we expected.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with many previous publications (Asbeck et al, 2019;Khanalizadeh et al, 2020;Kozak et al, 2018;Larrieu, Cabanettes, Brin, et al, 2014;Paillet et al, 2019;Regnery et al, 2013;Vuidot et al, 2011) we observed an increase in hazard rate with DBH (Courbaud et al, 2017;Jahed et al, 2020). In this study, bark-loss, crowndeadwood, cracks and dendrotelm showed a decrease in hazard rate with DBH, which means that these TreMs usually form for the first time on a tree when it is still small.…”
Section: Trem Formation During Tree Developmentsupporting
confidence: 92%
“…There are fewer studies on tree species such as Douglas fir (Pseudotsuga menziesii (Mirb.) Franco) or Oriental beech (Fagus orientalis Lipsky (Fo)) from outside Europe [52][53][54][55][56]. All these studies have in common that tree species is a determining factor of TreM abundance and richness.…”
Section: Determinants Of Tree-related Microhabitat Occurrencementioning
confidence: 99%
“…This step takes into account the ecological interactions and the reciprocal influence exerted by both the biotic and abiotic components, such as type and modality of regeneration, humus quality, internal microclimate of the forest, periodicity in the availability of nutrients, etc. [41][42][43][44]; c. estimation of the development trends of the forest species composition and structure within the 'Ecological Forest Units'; d. comparison of the models identified through time within similar EFUs and through spatial variability between different EFUs; e. selection of the EFUs with the more stable and ecologically efficient chronological series of structure development. These series show the models available within the forest or forested area to which refer planning and management.…”
Section: The Analytical Planning Schemementioning
confidence: 99%